Honouring the donor: in death and in life - Gillett, Grant (Journal of medical ethics, 2013)
Elective ventilation (EV) is ventilation—not to save a patient's life, but with the expectation that s/he will die—in the hope that organs can be retrieved in the best possible state. The arguments for doing such a thing rest on the value of the lives being saved by the donated organs, maximally honouring the donor's wishes where the patient can be reasonably thought to wish to donate, and a general principle in favour of organ donation where possible as an expression of human solidarity. Arguments against include difficulties surrounding the patient's consent to donation (including the risk of them surviving in an unacceptably bad state), the possibility of changing our perception of organ donation and care in dying, and the moral distress potentially caused to intensive care unit (ICU) staff involved in EV. EV can occur before or after the patient is declared dead and it is EV before the declaration of death (EVb) that occasions the ethical worries. I argue that when we acknowledge the tragedy involved, attend sensitively to the grief proper to human death, and ensure that we are not working in an ethical and legal climate that increases the likelihood of inadvertent survival in an unacceptably bad state, EVb is ethically defensible.